IMPLEMENTASI SISTEM INFORMASI PENJADWALAN DOKTER BERBASIS WEBSITE DI RUMAH SAKIT IBU DAN ANAK BRAWIJAYA MENGGUNAKAN METODE FIRST COME FIRST SERVE (FCFS) - Panji Henindya Nugraha; Dede Sahrul Bahri (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Optimal healthcare services in hospitals highly depend on a well-organized doctor scheduling system. At Brawijaya Mother and Child Hospital, the scheduling process is still carried out manually, making it prone to errors, delays, and inefficiencies in workflow. This study aims to design and implement a web-based doctor scheduling information system by applying the First Come First Serve (FCFS) method as the basis for queue scheduling. FCFS is chosen for its fair and straightforward approach in determining the order of service based on registration time, without any specific prioritization. The system development follows the waterfall methodology, which includes stages of requirement analysis, system design, implementation, testing, and maintenance. Technologies used in this system include PHP programming language, MySQL database, and supporting frameworks. The system features include doctor data management, practice scheduling, and online patient registration, accessible by both patients and hospital administrators through a user-friendly interface. The implementation results show that the system is capable of managing doctor schedules in a more structured manner, reducing schedule conflicts, and increasing efficiency in patient service processes. The presence of this information system accelerates administrative processes, improves transparency and accuracy, and supports the quality of services while enhancing patient satisfaction. This research is expected to provide a digital solution for hospitals in managing doctor schedules and to serve as a foundation for developing similar information systems in the future.